2016
DOI: 10.1016/j.jpowsour.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of battery testing protocols: Those used by the U.S. advanced battery consortium and those used in China

Abstract: Two testing protocols, QC/T 743 and those used by the U.S. Advanced Battery Consortium (USABC), were compared using cells based on LiFePO 4 /graphite chemistry. Differences in the protocols directly affected the data and the performance decline mechanisms deduced from the data. In all cases, the rate of capacity fade was linear with time. Overall, the testing protocols produced very similar data when the testing conditions and metrics used to define performance were similar. The choice of depth of discharge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The results of the formation tests are not reported often enough. Several strategies are available in the literature from C/3 discharge and 50% SOC resistance test [27] to protocols such as HNEI's initial conditioning characterization test (ICCT) [28][29][30][31]. Lasting less than a week, the ICCT consists only of C/2 and C/5 cycles, Figure 2, and serves two purposes.…”
Section: Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the formation tests are not reported often enough. Several strategies are available in the literature from C/3 discharge and 50% SOC resistance test [27] to protocols such as HNEI's initial conditioning characterization test (ICCT) [28][29][30][31]. Lasting less than a week, the ICCT consists only of C/2 and C/5 cycles, Figure 2, and serves two purposes.…”
Section: Formationmentioning
confidence: 99%
“…The caveat being that this rate must be less aggressive than the rate used in the duty cycling. The RPT protocol is limited to two cycles to minimize its toll on the cell SOH but additional rates or procedures (constant power, electrochemical impedance spectroscopy, full OCV vs. SOC test, different temperatures) [27,38,39] could be added if necessary. This is often done in the literature for the first RPT only.…”
Section: Reference Performance Testmentioning
confidence: 99%
“…Additionally, the identification results of the two fractional orders are shown in Figure 6e,f. The DST test [48] is a widely used dynamic driving profile to evaluate the performance of the vehicle, and is also used to validate model accuracy or algorithm efficiency [13,49]. In the test, the battery goes through several DST cycles with the SOC operational range from 90% to 20%.…”
Section: The Dynamic Stress Testmentioning
confidence: 99%
“…Zhang et al (2017) examined the technology differences in patents and found that China has paid more attention to electric vehicle technologies than the USA since 2001. Researchers have also compared test standards and protocols for PEVs; for example, PHEV energy consumption test regulations (Hou et al 2015) and traction battery test protocols (Robertson et al 2016). Gohlke and Zhou (2019) examined properties of PEVs sold in the USA from 2010 to 2018, exploring how vehicle sales, range, efficiency, battery materials, and cost evolved over time.…”
Section: Introductionmentioning
confidence: 99%